Ending the Silence of People with Little or No Functional Speech: Testifying in Court - Bryen, Diane Nelson; Wickman, Christopher H. (Disability Studies Quarterly, 2011)
Keywords crime, abuse, testify, court, speech disability, AAC Abstract Crime against people with developmental and other disabilities is similar in scope to that of women, children and the elderly. However, their victimization remains largely invisible and unaddressed (Bryen, Carey, & Frantz, 2005; Sobsey, 1994). Research from the United States indicates that people with developmental disabilities are four to 10 times more likely to be victims of a crime and that crimes against them are less likely to be reported or prosecuted (Martin, Ray, Sotres-Alvares, Kupper, Moracco & Dickens, 2006). Individuals with disabilities who have little or no functional speech face a double vulnerability when it comes to crime, abuse, and neglect as they are often the voiceless and invisible members of society (Bryen & Frantz, 2004; Bryen, Carey, & Frantz, 2005; Davies, 2002). The purpose of this study was two-fold: (1) describe court rulings in the United States that clarify the impact that having a little or no functional speech (LNFS) and relying on the use of AAC plays in testifying in court, and (2) describe the outcomes of court cases when someone with LNFS testifies in court as a witness in their own defence when they have been a victim of a crime. In order to accomplish these dual purposes, a comprehensive search of federal and state cases involving people with LNFS and their ability to successfully testify in court, a comprehensive search of federal and state cases involving people with LNFS and their ability to testify in court was performed using LexisNexis. The results of this study are discussed in terms of policies and practices that affect people with LNFS themselves, professionals who support them, and the court system.